Pelatihan Pengolahan Data Penelitian Menggunakan Eviews Untuk Meningkatkan Kualitas Karya Ilmiah Mahasiswa Di Universitas Tjut Nyak Dhien Medan - Mukarramah Mukarramah; Cindy Yolanda; T.M. Iqbal Chaira; Ulfa Utari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2024)
Research is one of the three components of the dharma of higher education. Research for students is presented in the final project, either the thesis or thesis, or is included as a mandatory requirement for graduation. From the results of observations made, there are still many students at Tjut Nyak Dhien University in Medan who are not yet proficient in using statistical testing tools, namely E-views. Based on these concerns, we took specific steps by implementing a community service program with the topic